Care during pregnancy and childbirth for migrant women: How do we advance? Development of intervention studies – The case of the MAMAACT intervention in Denmark. (April 2016) - Villadsen, Sarah Fredsted; Mortensen, Laust Hvas; Andersen, Anne-Marie Nybo
Abstract : The increased risk of adverse pregnancy and childbirth outcomes demonstrated for many non-Western migrants in Europe, Australia and North America may be due to inadequate use and suboptimal quality of care. It is indicated that a poor user–provider interaction leads to inequity of pregnancy and delivery care. This review demonstrated that there is no evidence of best practice antenatal care for migrant women. Health system interventions for improved maternal and child health among migrants should be based on thorough needs assessments, contextual understanding and involvement of the target group and health-care providers. We present the Danish MAMAACT study as a strategic perspective on how to move forward, and we describe methodological steps in intervention development. Based on a mixed method needs assessment, the MAMAACT study aimed to enhance the communication between migrant women and midwives during antenatal care regarding warning signs of pregnancy and how to access acute care. Highlights: We review the access to and quality of reproductive health care for migrants. Lack of interpretation and cultural competent communication hinder quality of care. There is no evidence for best practice health care for pregnant and delivering migrant women. Research in health system interventions could lead to better reproductive health. Contextual understanding and participatory approaches to intervention development are important.